Дистрибуція продукції підприємств високотехнологічного машинобудування України на ринках ЄС - Данько, Тарас Володимирович; Карачун, Ю. С. (НТУ "ХПІ", 2014)
Проаналізовано проблеми управління ланцюгами постачання продукції у системі міжнародної дистрибуції підприємств. Розглянуто особливості управління ланцюгами постачання високотехнологічних підприємств. Обґрунтовано доцільність дослідження поточного стану дистрибуції високотехнологічної продукції машинобудівних підприємств України на ринках ЄС. Вивчено залежність стану дистрибуції високотехнологічної продукції машинобудівних підприємств України на ринках ЄС від кількості країн, які охоплені збутом, та рівня зрілості управління ланцюгами постачання.

The problems of supply chain management products in the international distribution companies were analyzed. The features of supply chain management of high-tech enterprises were considered. Expediency of study of the current state of distribution of high-tech products of machine-building enterprises of Ukraine in the EU was grounded. Dependence of the state distribution of high-tech products of machine-building enterprises of Ukraine in the EU on the number of countries that are covered by sales, and on the maturity level of supply chain management was studied. The characteristics of distribution companies and their problems in the modern world. The application of these or other factors of production in the various markets of high-tech engineering. Offered a variety of markets in the EU to implement measures to improve supply chain of the product.
Ukraine's High Technology Machinery Companies Products Distribution to the EU Markets
Keywords: високотехнологічні галузі; зрілість управління; ланцюги постачання продукції; міжнародна дистрибуція; management maturity; product supply chains; distribution; EU markets; high-tech machine building